EFEKTIVITAS PROPAGUL FMA LOKAL PASANG SURUT ASAL INANG JAGUNG - Sefrila, Marlin; Lumbantoruan, Santa Maria; Adriansyah, Fikri; Kurnianingsih, Astuti; Darmawan, Arif Rizky (University of Prof. Dr. Hazairin, SH, 2024)
Suboptimal land such as tidal swamps is still quite widespread in Indonesia and has a low fertility level. This land requires good management to support optimal crop production. One management that still has the potential to be developed is the use of microorganisms, namely AMF. Use of AMF in tidal soil in the form of AMF inoculant as a natural biofertilizer. The aim of the research is to evaluate the effectiveness of local tidal AMF propagules produced during trapping on corn host plants which will be used later as biofertilizer. This study used a factorial randomized complete group design (RKLT). The first factor is the dose of local AMF propagules from the corn host plant (0, 5 and 10 g plant-1) and the second factor is the fertilization interval (1 and 2 times a week), with 3 replications for each treatment unit consisting of 20 plants. The application of AMF propagules showed an effect on plant height, leaf green level, shoot dry weight and percentage of AMF infection. The level of greenness of corn plant leaves was highest when 5 g of AMF propagules were given when compared with 10 g of AMF propagules and without AMF propagules. The increase in the percentage of infection of corn roots by AMF at 10 g of AMF propagules+1 time a week when compared with no AMF propagules+1 time a week and 5 g of propagules+fertilization 2 times a week was 50.67% and 46.34%.